2008
DOI: 10.1093/jxb/erm332
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in theArabidopsis SWC6gene, encoding a component of the SWR1 chromatin remodelling complex, accelerate flowering time and alter leaf and flower development

Abstract: Mutations affecting the Arabidopsis SWC6 gene encoding a putative orthologue of a component of the SWR1 chromatin remodelling complex in plants have been characterized. swc6 mutations cause early flowering, shortened inflorescence internodes, and altered leaf and flower development. These phenotypic defects resemble those of the photoperiod independent early flowering 1 (pie1) and early in short days 1 (esd1) mutants, also affected in homologues of the SWR1 complex subunits. SWC6 is a ubiquitously expressed nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
103
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(116 citation statements)
references
References 69 publications
(164 reference statements)
10
103
0
3
Order By: Relevance
“…14,25 Similarly, an effect on FLC expression by alterations in chromatin structure (while the expression of other genes is not changed) is also observed for defects in other Arabidopsis chromatin modifiers that promote chromatin-regulated transcription, including a chromatin-remodeling complex of the SWR1-type and the histone H3 methyltransferase SDG25. 28,29 Consistently, transcript profiling experiments revealed that defects in various chromatin modifiers, including HUB1 and SDG25, cause differential expression of only a subset of genes. 18,28 Experiments with various chromatin factors have demonstrated that proper expression of FLC appears to be complexity and different from those of elo or hub1 mutants (Fig.…”
mentioning
confidence: 79%
“…14,25 Similarly, an effect on FLC expression by alterations in chromatin structure (while the expression of other genes is not changed) is also observed for defects in other Arabidopsis chromatin modifiers that promote chromatin-regulated transcription, including a chromatin-remodeling complex of the SWR1-type and the histone H3 methyltransferase SDG25. 28,29 Consistently, transcript profiling experiments revealed that defects in various chromatin modifiers, including HUB1 and SDG25, cause differential expression of only a subset of genes. 18,28 Experiments with various chromatin factors have demonstrated that proper expression of FLC appears to be complexity and different from those of elo or hub1 mutants (Fig.…”
mentioning
confidence: 79%
“…For RT-PCR analysis, the HOS1-specific primers 59-TTGTCCTCTATTTGCGTTTGT-39 and 59-TCAAATTGGGGAA-GAAGTTATG-39 were designed to amplify the N-terminal part of the HOS1 coding region. The FLC, CO, FT, and SOC1 primers used were described elsewhere (Piñ eiro et al, 2003;Lá zaro et al, 2008). UBIQUITIN10 (UBQ10) was used as a loading control in these experiments.…”
Section: Expression Analysismentioning
confidence: 99%
“…In Arabidopsis (Arabidopsis thaliana), the complex has a major role in transcriptional regulation, as SWR1-C mutants exhibit a characteristic early-flowering phenotype due to the dysregulation of several developmental genes (Noh and Amasino, 2003;Choi et al, 2005;Deal et al, 2005;Lázaro et al, 2008;March-Díaz and Reyes, 2009). A role of Arabidopsis SWR1-C in DNA repair has only recently been documented.…”
Section: Chromatin-remodeling Complexes Connected With Ddrmentioning
confidence: 99%